2014
DOI: 10.17795/ajnpp-20314
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Tramadol Abuse Among College Students in West of Iran: an Application of the Theory of Planned Behavior

Abstract: Background:Tramadol is an opioid analgesic indicated for the treatment of moderate and severe pains. In the case of long administration, tramadol has a potential to cause dependency, tolerance and drug abuse. Objectives: This study aimed to investigate the prevalence and factors associated with tramadol abuse among college students based on the Theory of Planned Behavior (TPB) as a theoretical framework. Patients and Methods: This descriptive-analytical study was performed on 400 college students of Hamadan un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
9
1
Order By: Relevance
“…Some pharmacists also noticed that if tramadol was dispensed to one teenager, others would also request tramadol from their particular community pharmacy. This appears consistent with a previous report that the motivations of peers played a pivotal role in substance abuse among adolescents [22].…”
Section: Discussionsupporting
confidence: 93%
“…Some pharmacists also noticed that if tramadol was dispensed to one teenager, others would also request tramadol from their particular community pharmacy. This appears consistent with a previous report that the motivations of peers played a pivotal role in substance abuse among adolescents [22].…”
Section: Discussionsupporting
confidence: 93%
“…The level of tramadol abuse found in the current study is very high compared with findings by Bashirian et al [26], who reported a prevalence of 12.5% amongst college students in Iran. Another study in Sweden analyzed hair samples and reported a higher prevalence of 33% [27].…”
Section: Discussioncontrasting
confidence: 72%
“…During the first stage, the content domain of the construct was specified. In this stage, interviews were conducted with the experts (gynecologists and midwives) and pregnant women, and a review of the literature relating to the TRA [31][32][33][34][35] was performed to develop an item pool and content domain. The main dependent variable in the present analysis was the cesarean delivery method.…”
Section: Scale Development Processmentioning
confidence: 99%